Structural and electrical characterization studies for ternary composite of polypyrrole - Megha, R.; Ravikiran, Y. T.; Kumari, S. C. Vijaya; Prakash, H. G. Raj; Revanasiddappa, M.; Manjunatha, S.; Dastager, Syed G.; Thomas, S. (Journal of Materials Science-Materials in Electronics, 2020)
In this work, temperature dependence of alternate current (AC) and direct current (DC) conductivities of optimized polypyrrole/silver-tantalum oxide (PPy/Ag-Ta2O5), a ternary conducting polymer composite is comparatively studied with those of PPy and PPy/Ag. For the purpose, silver (Ag) nanoparticles were encapsulated with polypyrrole (PPy) by in situ oxidative polymerization to form core-shell structured PPy/Ag composite for which Ag nanoparticles were extracted from green tea. The PPy/Ag composite was then mechanically mixed with tantalum pentoxide (Ta2O5) to form PPy/Ag-Ta(2)O(5)ternary composite. Increase in depth of delocalization band of PPy in ternary composite as compared to those of PPy/Ag composite and PPy, indicating its increased AC conductivity confirmed from the comparative FTIR analyses. Interaction between PPy/Ag composite and Ta(2)O(5)in the ternary composite was confirmed from XRD studies. The formation of core-shell structured PPy/Ag composite and Ta(2)O(5)particles embedded in such PPy/Ag composite to form PPy/Ag-Ta(2)O(5)ternary composite confirmed from TEM and Raman studies. The frequency- and temperature-dependent electrical conductivity studies revealed increase in AC conductivity of the ternary composite as compared to those of PPy/Ag composite and pure PPy attributed mainly to interfacial effects. The charge transport in these samples predicted to be due to correlated barrier hopping of charges was confirmed by calculating their respective AC and DC activation energies.